Social Economic study of farmer of Padi Penangkar In Kenagarian Sungai Dareh Pulau Punjung Distric Of Dharmasraya Regency - Putra, Eridal; Drs. Dasrizal, MP, Drs. Dasrizal, MP; Zuriyani, M.Si, Elvi (Pendidikan Geografi, 2014)
ABSTRACTThe purposes of this research to get data, analyze and discuss about the farmer concieted economic at Sungai Dareh homeland, Pulau Punjung subdistrict Dharmasraya Regency that investigate from 1). Condition of income. 2) condition of education. 3) Housing condition. 4) social interaction.This research was descriptive research with use percentage formula. The population of this were farmers that live at sungai dareh homeland subdistrict of pulau punjung Dharmasraya Regency 112 persons of population. The respondent of the sample this research 112 all of population. Sample of this research with use totaly sampling. The data collection of with structural of questionairre.The finding of this research as follow: 1) condition income of the farmer concieted at sungai dareh homeland, pulau punjung subdistrict, Dharmasraya regency as central income of her husband that available of foods , expulsion foods > Rp 1.000.000-Rp.1.250.000 and expulsion each month avarrage < Rp 1.000.000-Rp 1.250.000. 2) condition of education the farmer at homelandt of sungai dareh, pulau punjung subdistrict Dharmasraya Regency graduated of senior high school. 3) condition of housing of the farmers concieted at sungai dareh homeland, pulau punjung subdistrict Dharmasraya regency as general liveat their house, the condition of building was permanent with total of rooms 3 bedrooms and the lighting of their house from PLN. The social relation of the farmers conciated at sungai dareh homland, subdistrict of pulau punjung, Dharmasraya Regency categories the best.